Performance Evaluation of ns-3 Real-Time Emulation - Ottens, Martin; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (IEEE Access, 2025)
With its real-time mode and tap-bridges, the network simulator ns-3 offers the possibility to integrate real applications or even hardware into a testbed in which ns-3 emulates the network topology. This eliminates the need to develop separate simulation models. However, there are several differences compared to a model-based discrete event simulation, where applications and network topology run together in the simulation process without real-time constraints. Using ns-3 to build an emulation environment makes it necessary to run in real-time mode, which results in considerable limitations with regard to the achievable throughput and the complexity of the simulated topology. This paper compares the performance that researchers can expect from pure model-based simulations and ns-3-based emulation environments. For this, we evaluate the impact of differently complex network topologies and applications on the simulator throughput in a minimal emulation setup. All measurements are compared with a pure model-based simulation setup. The performance of our setup is measured by the number of possible TCP and UDP flows. With complex network topologies and applications, only a few flows can be handled. In contrast, with simple topologies and applications, the measured throughput of our emulation setup is between 14 Mbps and 120 Mbps. We demonstrate that the achievable throughput additionally depends on ns-3 build profiles and CPU characteristics, highlighting, in particular, the impact of packet throughput as a limiting factor.
Keywords: Real-time systems; Network topology; Emulation; Topology; Performance evaluation; Throughput; Routing protocols; Computational modeling; Complexity theory; Codes